Powder metallurgical materials and products. Methods of testing and chemical analysis of hardmetals. Chemical analysis by flameatomic absorption spectrometry. Determination of cobalt, iron, manganese, molybdenum, nickel, titanium and vanadium in contents from 0.5% to 2% ($7Im/m$7R) Part 4.17.5, (30th June 1986) - British Standards Institution,
No abstract available